Dysbetalipoproteinaemia : clinical and laboratory aspects, changes in lipoprotein composition and remnant metabolism associated with lipid lowering drugs - Blom, Dirk Jacobus (Department of Medicine, 2014)
Includes bibliographical references (p. 483-539).